The impact of national values on the prevention and control of COVID-19: An empirical study - Lyu, Yanwei; Zhang, Jinning; Wang, Yue (Frontiers in Psychology, 2022)
The outbreak of COVID-19 at the end of 2019 has become the most devastating public health event of the 21st century. The different performances of governments and people in different countries and regions show that national values may play an important role in the prevention and control of COVID-19. Based on data from the seventh wave of World Values Survey (WVS-7) and the Human Freedom Index (HFI) report in 2020, three national value factors are extracted in this paper, including religious belief, government satisfaction and individual freedom. Then OLS regression model is constructed to explore the influence of these three value factors on the prevention and control of COVID-19 and some heterogeneity analysis is implemented. The results show that religious belief and individual freedom significantly increased the COVID-19 infection rate, while government satisfaction significantly reduced the COVID-19 infection rate. The study findings have the ability to hold up after a range of robustness. For countries and regions with different COVID-19 testing policies, the influence of national values is different. Only in countries and regions with high testing rate policies and complete systems of the prevention and control of COVID-19, the influence of national values is significant. Based on these findings, a series of targeted policy recommendations for building national values in the post-epidemic era are proposed.